Lexical Richness of Students’ Writings - Dwi Indarti (Wanastra: Jurnal Bahasa dan Sastra, 2021)
The present study compares the lexical richness of 30 essays taken from the same class of University of Bina Sarana Informatika (henceforth mentioned as UBSI)’s students.  The 30 essays were written by female and male of English Department students during their first, second, and third semester. This paper uses Web-based Second Language (L2) Lexical Frequency Profile (LFP), a batch mode of the web-based interface to the lexical richness proposed by Laufer and Nation (1995) which allows the users to calculate and to analyze the lexical richness of a corpus of text files at one time.  The focus of this study is merely on the score of tokens, types and type-token ratio (TTR). The results show that the average of tokens produced by male students is higher than female students. In term of types, the average types of female students are lower than male students. Meanwhile, the highest TTR score was gained by female students (0.60) and the lowest TTR score was produced by male students (0.55), both in the second semester. A big TTR Score indicates a high lexical richness, while a small TTR shows a low lexical richness. By comparing the lexical richness of students’ writings, this study is expected to show the students’ writing skill improvement or impairment during first three semesters of studying English.